SELF-CARE MANAGEMENT AND SOCIAL SUPPORT AMONG PEOPLE WITH TYPE 2 DIABETES ATTENDING SELECTED DIABETES CLINICS IN POKHARA - Gurung, Anita; Paudel, Kalpana; Thapa, Nirupa; Pokhrel, Nabina (Journal of Chitwan Medical College, 2024)
Background: Social support plays a significant role in determining the self-care management of individuals with diabetes. In the developing countries, the association between two factors has not been adequately explored. This study assessed the level of self-care management and social support among individuals with type 2 diabetes and identify associations between self-care management, social support, and selected variables. Methods: In this multisite cross-sectional study, 158 individuals with type 2 diabetes who attended selected diabetes clinics in Pokhara Nepal, were selected using a nonprobability purposive sampling technique from February 10 to March 10, 2021. Data collection was conducted through interviews using a modified summary of diabetes self-care activities and a multidimensional scale of perceived social support as instruments. A descriptive analysis followed by an inferential statistical test was performed to assess the association between variables. Results: More than half (53.2%) of respondents had satisfactory levels of diabetes self-care management, and most of them received high levels of social support. Levels of self-care management were significantly associated with the levels of social support. Marital status, family income, residency, educational status, disease duration, regular follow-up visits, A1C goal, and co-morbidity were significantly associated with self-care management. Gender, marital status, and follow-up visits were significantly associated with the level of social support. Conclusions: Focusing on enhancing social support, including the self-care management of individuals with diabetes, can force diabetes management more successful. Health professionals should implement programs for individuals with diabetes, including peer support groups, family education, and community-based initiatives.